The acceptability of volunteer, repeat blood donations in a hospital setting in the Adamaoua region of Cameroon. Issue 6 (29th September 2014) - Rolseth, S.; Stange, P.; Adamou, D.; Roald, B.; Danki‐Sillong, F.; Jourdan, P.
SUMMARY Background and Objectives The knowledge of factors that may influence blood donation in Cameroon is limited. The objectives of this study are to assess the characteristics of previous and potential blood donors by exploring the religious beliefs, and knowledge and understanding of blood donations among individuals present at a district hospital. Materials and Methods Forty‐nine in‐depth, semi‐structured interviews were conducted among consenting, randomly selected 18 years or older community members present at a district hospital in the Adamaoua region during October and November 2011. Results Ninety‐eight per cent (48/49) of the individuals present at this district hospital had heard of blood transfusions. Forty‐seven per cent (23/49) had not previously been asked to donate blood; however, 94% (44/47) said that they would donate if given the opportunity. Thirty‐three per cent (16/49) had previously donated blood to family members or for replacement, and 81% of these said they would repeat donations. The majority of both donors and non‐donors were motivated to donate blood for altruistic reasons. Conclusion The findings suggest that community members present at this district hospital in Cameroon may be recruited for repeat blood donations. Although the altruistic motivation to donate blood suggests that donors could be recruited from a district hospital population, targeted information about blood donations and accessible blood transfusion services need to be put in place. The study may add to the understanding of the preconditions for blood donations and the possibility to establish sustainable blood transfusion services in the Adamaoua region in Cameroon.